Solanum diphyllum L. (Solanaceae): A new addition to the Flora of Uttarakhand, India - Sharma, Ishwar Prakash; Saxena, Parul; Gond, Deepak; Patel, Shambhu P.; Balkrishna, Acharya (Indian Forester, 2019)
No Abstract.